Factors Influencing the Interest of Prospective Students in Choosing the D3 Accounting Program at Politeknik Negeri Banjarmasin - Priyougie Priyougie; Ahsanul Hag; Rusniati Rusniati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Prospective students who wish to enter higher education must first choose the study program they desire, as this program will provide them with the knowledge and skills needed for their future. Selecting a study program may seem easy for prospective students, given the wide range of options available at a university. However, they also need to consider other factors, both internal and external, when making their choice. This study aims to identify the factors that influence the interest of prospective students in choosing the D3 Accounting Program at Politeknik Negeri Banjarmasin and to provide information regarding the profile of respondents based on student status, gender, and the level of decision-making in selecting the D3 Accounting Program at Politeknik Negeri Banjarmasin. The data analysis techniques used in this study include descriptive analysis, instrument testing, classical assumption testing, and hypothesis testing to analyze the effect of two or more independent variables on the dependent variable using regression equations for two or more variables. The t-test is used to examine the significance of each independent variable's constant, determining whether each variable has a partial (individual) effect on the dependent variable, while the F-test is used to assess the simultaneous impact of the independent variables on the dependent variable, determining whether the influence is significant or not. The results of the hypothesis testing using the F-test and t-test indicate that all alternative hypotheses (Ha) are accepted, and null hypotheses (Ho) are rejected. Thus, the findings reveal that social factors, job opportunities, accreditation, and education costs collectively influence the interest of prospective students in choosing the D3 Accounting Program at Poliban